Soil enzymes associated with carbon and nitrogen cycling in invaded and native secondary forests of northwestern Argentina - Aragón, Myriam Roxana (2014)
Background and aims Alien success has frequently been associated with changes in the concentrations of soil nutrients. We aim to investigate the effects of plant invasion on soil nutrients, potential enzyme activity and litter elemental composition and stoichiometry. Methods We compared stands of secondary forest invaded by Ligustrum lucidum and those dominated by natives, and performed litter chemical analyses on 3 native and 2 exotic tree species. Results Soils of invaded sites had 20 and 30 % increase in β-glucosidase and alkaline phosphatase activity, higher Olsen-phosphorus (P) and potassium (K) concentrations and lower nitrogen (N) concentration and N:P, N:K and ammonium:Olsen-P ratios. Invaded and non-invaded sites differed in their overall nutrient composition and enzyme activity. Natives and exotics differed in nine of the 16 litter elemental composition and stoichiometry variables analyzed. Conclusions The low N:P ratio in litter, the decrease in soil N in invaded stands and the low N concentration of exotics suggest that N is the limiting nutrient and that exotic success is related to higher N uptake and use efficiency. The higher investment in the acquisition of soil resources, higher nutrient uptake and use efficiency of limiting nutrients contribute to the success of exotics in this subtropical forest.